ʻAnusō̜n ngān phrarātchathān phlœ̄ng sop Phrakhrū Bō̜rihānkitkōson (Lūangphō̜ Kō̜nthō̜ng ʻInthawangsō), ʻadīt čhaoʻāwāt Wat Khōn, ʻŌ̜. Prakhōnchai, Čhō̜. Burīram, ʻadīt Thīprưksā Čhao Khana ʻAmphœ̄ Bān Krūat ([Khrō̜pkhrūa Sinthusakun], 2011)
Cremation volume comprises a brief biography and some Buddhist teachings; volume brought out to commemorate Phrakhru Borihankitkoson (Luangpho Konthong Inthawangso), a Thai senior monk, former abbot of Wat Khon in Buriram Province, Northeastern Thailand.